2020
DOI: 10.1080/13548506.2020.1861314
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 pandemic fear, life satisfaction and mental health at the initial stage of the pandemic in the largest cities in Poland

Abstract: The study investigated whether the level of life satisfaction and general mental health was associated with COVID-19 worries at the initial stage of the COVID-19 pandemic in Poland. A cross-sectional observational study using an online questionnaire was conducted between 19 March and 27 April 2020, i.e. at the beginning of the epidemic in Poland. The study participants were residents of Poland over the age of 18 years. A total of 412 completed responses were received. The majority of respondents were women (75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 7 publications
3
47
1
Order By: Relevance
“…A Polish study conducted at the beginning of the pandemic, in spring 2020, showed that 68% of respondents were worried about the COVID-19 pandemic. The main areas of concern were: death of loved ones (75%), severe illness in loved ones (72%), failure of healthcare (64%), and individual and social consequences of the pandemic (64% and 63%, respectively) [ 43 ]. Polish research indicates that 30% of respondents changed their alcohol drinking habits during the pandemic: 14% consume more alcohol and 16% consume less [ 44 ].…”
Section: Effects Of the Covid-19 Pandemic On Public Mental Health In Polandmentioning
confidence: 99%
“…A Polish study conducted at the beginning of the pandemic, in spring 2020, showed that 68% of respondents were worried about the COVID-19 pandemic. The main areas of concern were: death of loved ones (75%), severe illness in loved ones (72%), failure of healthcare (64%), and individual and social consequences of the pandemic (64% and 63%, respectively) [ 43 ]. Polish research indicates that 30% of respondents changed their alcohol drinking habits during the pandemic: 14% consume more alcohol and 16% consume less [ 44 ].…”
Section: Effects Of the Covid-19 Pandemic On Public Mental Health In Polandmentioning
confidence: 99%
“…The outbreak of coronavirus disease in late December 2019 in China quickly became an emerging situation, rapidly spreading outside China, which in March 2020 was declared as a pandemic by the World Health Organization [1]. This pandemic is having a major impact not only on people's physical health but also on mental and sexual well-being [8,9]. As far as we are aware, our study is the first to investigate the intentions for parenthood amongst adult Polish people during the COVID-19 outbreak.…”
Section: Discussionmentioning
confidence: 99%
“…Further, there is a varying amount of evidence available in English for a global audience from different geographies. For example, while there is some limited information available about the mental health consequences of COVID-19 in Central and Eastern Europe (28)(29)(30), studies on pandemic-related mental health interventions are lacking.…”
Section: Introductionmentioning
confidence: 99%